Capsule Commentaries. - Hendrickson, Harvey S.; Walther, Larry M.; Zéghal, Daniel; H. S. H.; Wiskeman, Richard H.; Simon, Daniel T.; Schultz, Norman O.; Murdock, Richard J.; Moriarity, Shane; Braiotta, Louis; Dillaway, Manson P. (The Accounting Review, 1986)
Abstract Reviews various books related to accounting. "Advanced Accounting," 3rd ed., by Floyd A. Beams; "Three Degrees Above Zero: Bell Labs in the Information Age," by Jeremy Bernstein; "Wiley-Ronald Auditing Service," by D.R. Carmichael and Martin Benis; "Dictionary of Accounting Terms," by Derek French.